Improving Scientific Understanding in Early Childhood through Interactive Color Mixing Activities - Maku, Karmelia Rosfinda Meo; Meka, Marsianus; Mere, Veronika Owa (Universitas Pendidikan Ganesha, 2024)
Early childhood is characterized by diverse cognitive, motor, and interest development, which significantly influences their ability to understand scientific concepts. While some children can grasp scientific concepts with ease, others require more tailored learning approaches to support their development. This study aims to enhance children's scientific abilities, particularly in understanding the concept of color mixing, through the application of the color-mixing method. The research employed a Classroom Action Research (CAR) design conducted over two cycles. The subjects of the study were early childhood students in Group B during their second semester. Data on children's scientific abilities regarding color mixing were collected through observation using structured observation sheets. The data were analyzed using quantitative descriptive statistical techniques. The findings revealed a significant improvement in children's scientific abilities. In the first cycle, 65% of children were categorized as achieving a medium level, whereas in the second cycle, 100% of children reached a high level. This indicates a 35% increase in children's scientific abilities related to color mixing. The results demonstrate that the color-mixing method is effective in fostering children's understanding of scientific concepts while optimally supporting their cognitive development. This study offers practical insights, suggesting that interactive and contextual learning approaches can be an effective strategy for enhancing scientific abilities in early childhood education.